Manayunkia speciosa Leidy (Polychaeta: Sabellidae): introduction of this nonindigenous species in the Neotropical Region (Uruguay river, South America) - Armendáriz, Laura Cecilia (2010)
We report the migration of Manayunkia speciosa from its distribution in North America into the Neotropical Region (Argentina). We collected specimens from November 2007 to March 2009 in the lower Uruguay River-at 33° 5.01′S 58° 12′W, 33° 5.9′S 58°25.2′W from sediments reaching densities of 2,890 ind. m−2, at a mean abundance of 350 ind. m−2. Introductions of nonindigenous species, resulting intentionally or accidentally from anthropic activities, cause significant changes in ecosystems. In aquatic environments, polychaetes are a key invasive group that increases the geographical range of several species through human activities. M. speciosa may have reached the Rio de la Plata Basin through a shipping vector and thereafter the Uruguay River by self-navigation.